Shaping the attitudes of Russian managers in ethical issues - personal attributes and environmental pressure - Oberhauser, Marc; Holtbrügge, Dirk; Gurkov, Igor (International Journal of Emerging Markets, 2022)
Purpose The purpose of this study is to investigate how the attitudes of Russian managers are affected by personal attributes, environmental conditions and also cognitive processes. Design/methodology/approach Based on social cognitive theory, the authors developed hypotheses and tested them against data collected from 173 Russian managers via an online survey. A linear regression analysis revealed several determinants of ethical attitudes within the Russian context. Findings The findings suggest that personal values (i.e. political orientation), environmental conditions (i.e. hierarchical level, ownership - state-owned versus private - of the current employer, industry in which a manager works) as well as cognitive processes (i.e. the presence (absence) of multilingualism at the workplace) strongly affect ethical attitudes of Russian managers in several issues related to both job ethics (relations inside the organization) and business ethics (relations outside the organization). Practical implications Revealing a positive effect of multilingualism as cognitive process on managers' ethical attitudes, this study calls for incorporating a second lingua franca, for example, English, within the working context. Originality/value The study provides an in-depth investigation of the determinants of ethical attitudes in Russia. Conducting a single-country study, the authors are able to reveal locally meaningful determinants that may otherwise be overlooked.
CRIS-Team WoS Importer:2022-02-18